REALITAS SOSIAL DALAM NOVEL JANJI KARYA TERE LIYE - Fatmawati; Jawa Bhaga, Bertholomeus; Istiqomah, Afifah; Haryati, Gustia; Safaah, Tusana Nurul (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literary works contain sosial realities that represent human life and the universe. The purpose of this study is to describe the sosial reality contained in Tere Liye's Janji novel. The approach used to examine the novel is a mimetic approach. This approach is used because this approach views literature as an imitation of the universe. The research method used is descriptive qualitative. The data source for this research is the novel Promise by Tere Liye. The research data is in the form of quotations contained in the dialogues and monologues in the novel that are related to sosial reality. Data collection was carried out through several stages, namely reading carefully, making data transcripts that contain sosial reality, codifying data, then reducing and analyzing. The data analysis technique used is the interactive analysis which includes data reduction, data presentation, and verifying and drawing conclusions. Based on the results of the study, the sosial realities that emerge are aspects of culture, oppression, economy, religion, and education. The sosial reality shown in the novel is a representation of real everyday life. These things are a reflection of real life in society which become sosial facts.